Industria 4.0 y la digitalización hacia la satisfacción laboral de las organizaciones en Tampico, Tamaulipas, México; Industry 4.0 and digitization towards job satisfaction of organizations in Tampico, Tamaulipas, Mexico - Marco Antonio Díaz Martínez; Reina Verónica Román Salinas; Ariadna Dauleta Santiago Santiago; Catalina Mejía Barrios; Ricardo Zárate Cruz (Revista de Métodos Cuantitativos para la Economía y la Empresa, 2020)
– Industry 4.0 is related in each place and with the use and implementation of new technologies for the continuous improvement of administrative processes. As part of the growth of an organization, it is important that day by day it adapts to technological changes that affect worker operations or job security. Some of the elements that this industry encompasses are the use of autonomous equipment, robotics, process simulators, 3D printers, artificial intelligence and equipment that share information in real time. The objective of this article is to assess the digitization processes of organizations in the city of Tampico, Tamaulipas (Mexico), from the user's point of view, to identify the determining factors of job satisfaction. The multivariate technique of partial least squares regression (or PLS, by Partial Least Squares (or SEM, by Structural Equation Models) is used, considering as digitization analysis factors and their relationship with the relationship and collaboration model, skills and competencies professionals, digital training and digitization processes. The results show that the degree of motivation increases with the increase in the digitization of processes and that digital training and professional competencies need to increase gradually to have a positive impact in relation to the processes of digitization.
Keywords: C4; C5; L00; L7; L80; L84; 330; Industry 4.0; continuous improvement; organizational conditions; Cronbach's alpha